2023
DOI: 10.1093/ofid/ofad005
|View full text |Cite
|
Sign up to set email alerts
|

Partial-Oral Antibiotic Therapy for Bone and Joint Infections in People With Recent Injection Drug Use

Abstract: Background Limited outcome data exists regarding partial-oral antibiotic therapy, defined as oral antibiotics as part of a patient’s treatment, for bone and joint infections (BJI) in people who inject drugs (PWID). Methods We conducted a retrospective study of all PWID reporting drug use within three months and BJI requiring six or more weeks of antibiotics in an urban safety-net hospital between February 1, 2019 and February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Several institutions have previously published their experience using oral antibiotics, either to treat orthopedic infections in general 13 , 14 , 23 or in specific situations. 24 26 Similar to the current study, many of these institutions made a concerted effort to consider oral antibiotics for the treatment of orthopedic infections and saw a subsequent increase in the proportion of patients discharged on oral antibiotics. Also similar to the current study, no studies have found any increased risk of treatment failure when using PO versus IV antibiotics.…”
Section: Discussionmentioning
confidence: 69%
“…Several institutions have previously published their experience using oral antibiotics, either to treat orthopedic infections in general 13 , 14 , 23 or in specific situations. 24 26 Similar to the current study, many of these institutions made a concerted effort to consider oral antibiotics for the treatment of orthopedic infections and saw a subsequent increase in the proportion of patients discharged on oral antibiotics. Also similar to the current study, no studies have found any increased risk of treatment failure when using PO versus IV antibiotics.…”
Section: Discussionmentioning
confidence: 69%
“…Details of this cohort were previously published. 5 Demographics, recent substance use, and treatment outcomes were determined via review by a single coder of clinical notes from infectious diseases, addiction medicine, and/or admitting team. t Tests and χ 2 tests were used to compare demographics between opioid and stimulant co-use versus opioid-only.…”
mentioning
confidence: 99%
“…Patients were admitted to a university-affiliated urban teaching hospital in King County, Washington, throughout a 2-year study period (2019–2021). Details of this cohort were previously published 5 . Demographics, recent substance use, and treatment outcomes were determined via review by a single coder of clinical notes from infectious diseases, addiction medicine, and/or admitting team.…”
mentioning
confidence: 99%